Шумерско-хурритский словарь из Рас-Шамры как источник по хурритской диалектологии - Хачикян, M. JI.
Chačikjan, M.I.; A Sumero-Hurrian Vocabulary from Ras-Shamra as a Dialectological Source; engl. Résumé.